Application of Molecular Modelling and EPR Spectroscopy to Lipid Membranes – a Combined Approach - Catte, A.; V. S. Oganesyan
Knowledge of molecular interactions, thermodynamics, temperature and system composition effects are crucial for understanding the role that different lipids play in vital life processes in biological membranes. This knowledge is also important for understanding the impact that electromagnetic fields have on the order and mobility of molecules in lipid bilayers. The last decade has seen radical improvement in the molecular modelling of complex molecular and bio-molecular systems including lipid bilayers using Molecular Dynamics (MD) simulation techniques. MD simulations are now much faster and more accurate allowing researchers to predict complex molecularphenomena using actual structures.In this paper we present our recent results on the application of large scale MD simulations to phospholipid bilayers under different composition and conditions.Examples include: both all-atom and coarse-grain large scale MD simulations of binary and ternary compositions of lipid bilayers, modelling of the penetration of gas molecules (O2) in lipid bilayers, the effects of antimicrobial peptides on biological membranes, separation of lipid microdomains as a model for the study of lipid rafts. We also report MD simulations on lipid bilayers doped with structurally different nitroxide spin probes that are employed inexperimental variable temperature EPR spectroscopy. Finally, our recent preliminary results of all-atom MD modelling of the lipid bilayers subjected to microwave electric fields are also presented and discussed.
Keywords: Physics; Cross-Disciplinary